Spatio-temporal dynamics and trend forecasting of urban green high-quality development: An examination of 287 cities in China - Tonghui Yu; Shanshan Jia; Xufeng Cui (PLoS ONE, 2025)
Facing the dual challenges of economic growth and environmental conservation, advancing urban green high-quality development (UGHQD) is crucial for sustainable urban development. Rooted in the concept of UGHQD, this study develops a multidimensional evaluation indicator system encompassing economic development, social progress, and ecological civilization. By applying spatial autocorrelation analysis, cold and hot spots analysis, standard deviation ellipse, and Kernel density estimation, it examines the spatial distribution and dynamic evolution of UGHQD across China and its four major regions (Eastern, Central, Western, and Northeastern) from 2003 to 2020. It also forecasts the trajectory of UGHQD from 2021 to 2025. The research findings indicate: (1) A steady annual increase in the overall level of UGHQD, with a geographic pattern showing high levels in the east, moderate in the center, and low in the west. (2) A spatial agglomeration in UGHQD, predominantly in the eastern region, demonstrating spatio-temporal inertia. (3) Varying degrees of a “right-tail” phenomenon in the UGHQD across China and its four sub-regions, indicating a polarization trend or even a weak multi-polarization trend. (4) A forecast of continuous, steady growth in UGHQD from 2021 to 2025, with the eastern region maintaining its leading position. This study offers insights that enhancing our understanding of the fundamental concepts underlying UGHQD, providing a practical foundation and policy guidance for future collaborative efforts in enhancing urban development quality.